Influence of sensitization and allergen provocation procedures on the development of allergen-induced bronchial hyperreactivity in conscious, unrestrained guinea-pigs - R. E. Santing; C. G. Olymulder; B. van Diepen; H. Meurs; J. Zaagsma (Hindawi Limited, 1995)
The effects of different sensitization and allergen provocation regimens on the development of allergen-induced bronchial hyperreactivity (BHR) to histamine were investigated in conscious, unrestrained guinea-pigs. Similar early and late phase asthmatic reactions, BHR for inhaled histamine after the early (6 h) as well as after the late reaction (24 h), and airway inflammation were observed after a single allergen provocation in animals sensitized to produce mainly IgG or IgE antibodies, respectively. Repeating the allergen provocation in the IgE-sensitized animals after 7 days, using identical provocation conditions, resulted in a similar development of BHR to histamine inhalation. Repetition of the allergen provocation during 4 subsequent days resulted in a decreased development of BHR after each provocation, despite a significant increase in the allergen provocation dose necessary to obtain similar airway obstruction. The number of inflammatory cells in the bronchoalveolar lavage was not significantly changed after repeated provocation, when compared with a single allergen provocation. Finally, we investigated allergen-induced bronchial hyperreactivity by repetition of the sensitization procedure at day 7 and 14 (booster), followed by repeated allergen provocation twice a week for 5 weeks. Surprisingly, no BHR to histamine could be observed after either provocation, while the number of inflammatory cells in the bronchoalveolar lavage fluid after 5 weeks was enhanced compared with controls. These data indicate that both IgE and IgG sensitized guinea-pigs may develop bronchial hyperreactivity after a single allergen provocation. Repeated allergen exposure of IgE sensitized animals causes a gradual fading of the induced hyperreactivity despite the on-going presence of inflammatory cells in the airways, indicating a mechanism of reduced cellular activation.